Efficacy of plasma exchange in patients with anti-MDA5 rapidly progressive interstitial lung disease. Issue 133 (December 2022) - Bay, Pierre; de Chambrun, Marc Pineton; Rothstein, Vincent; Mahevas, Matthieu; De Prost, Nicolas; Roux, Antoine; Zuber, Benjamin; Biet, Dominique Israël; Hervier, Baptiste; Tazi, Abdellatif; Mouthon, Luc; Mekinian, Arsène; et al.
Abstract: Background: Rapidly progressive interstitial lung disease (RP-ILD) is a frequent and severe manifestation of anti-MDA5 dermatomyositis (MDA5-DM) associated with poor outcome. The optimal treatment regimen for MDA5-DM RP-ILD is yet to be determined. Specifically, the value of adding plasma exchange (PLEX) to corticosteroids and immunosuppressants remains unclear. We aimed to evaluate the effect of PLEX on the outcome of patients with MDA5-DM RP-ILD. Methods: This French nationwide multicentre retrospective study included all MDA5-DM RP-ILD patients from 2012 to 2021 admitted to 18 centres. The primary endpoint was one-year transplant-free survival. Results: 51 patients with MDA5-DM RP-ILD (female 67%; mean age at disease onset: 51 ± 11.6 years) were included. Thirty-two (63%) patients required mechanical ventilation and twenty-five (49%) received PLEX. One-year mortality or lung transplant occurred in 63% cases after a median follow-up of 77 [38–264] days. The Cox proportional hazards multivariable model only retained mechanical ventilation but not PLEX (p = 0.7) as independent predictor of the primary endpoint. One-year transplant-free survival rates in PLEX + vs. PLEX-were 20% vs. 54% (p = 0.01), respectively. The Kaplan–Meier estimated probabilities of one-year transplant-free survival was statistically higher in PLEX-compared to PLEX + patients (p = 0.05). PLEX + compared to PLEX-patients more frequently received mechanical ventilation and immunosuppressants suggesting PLEX + patients had a more severe disease. Conclusion: MDA5-DM RP-ILD is associated with poor rate of one-year transplant-free survival. The use of PLEX was not associated with a better outcome albeit they were mainly given to more severe patients. While our study reports the largest series of MDA5-DM RP-ILD given PLEX, these results needs to be interpreted with caution owing the numerous selection, indication and interpretation bias. Further studies are needed to evaluate their efficacy in this setting. Highlights: MDA5-DM RP-ILD is associated with poor rate of one-year transplant-free survival. The use of PLEX in MDA5-DM RP-ILD was not associated with a better outcome. Further studies on the role of PLEX in MDA5-DM RP-ILD are urgently awaited.